Detecting radiation esophagitis using 18F-FAPI-04 PET/CT in patients with LA-ESCC treated with concurrent chemoradiotherapy - Xinying Hu; Chao Han; Mingquan Zhang; Jing Jia; Zhengshuai Mu; Zheng Fu; Kailin Qiao; Jinming Yu; Yuchun Wei (BMC Cancer)
Abstract Purpose This prospective study examined whether 18F-AlF-NOTA-fibroblast activation protein inhibitor (FAPI)-04 (denoted as 18F-FAPI-04) positron emission tomography/computed tomography (PET/CT) can detect the development and severity of radiation esophagitis (RE) in patients with locally advanced esophageal squamous cell carcinoma (LA-ESCC) treated with concurrent chemoradiotherapy. Materials and methods From June 2021 to March 2022, images were collected from LA-ESCC patients who underwent 18F-FAPI-04 PET/CT examinations before and during radiotherapy. The development of RE was evaluated weekly according to Radiation Therapy Oncology Group criterion. The target-to-background ratio in blood (TBRblood) was analyzed at each time point and correlated with the onset and severity of RE. Factors that predicted RE were identified by multivariate logistic analyses. Results Thirty patients were evaluated. Significantly higher TBRblood (during radiotherapy, P = 0.003) and change in TBRblood compared with pre-RT (ΔTBRblood, P = 0.002) were observed in patients with RE than patients without RE. Those with grade 3 RE had a significantly higher TBRblood (during radiotherapy, P = 0.003) and ΔTBRblood (P = 0.003) compared with those with RE < grade 3. On multivariate analysis, ΔTBRblood was identified as a significant detection of any grade RE (P = 0.021) and grade 3 RE (P = 0.038). Conclusion The ΔTBRblood on 18F-FAPI-04 PET/CT may be effective at identifying patients with RE, especially grade 3 RE.